A network meta-analysis of direct factor Xa inhibitors for the treatment of cancer-associated venous thromboembolism. (February 2022) - Brandão, Gustavo Muçouçah Sampaio; Malgor, Rafael D; Vieceli, Tarsila; Cândido, Raissa Carolina Fonseca; Inácio, José Francisco Secorun; Rodrigues, Clarissa Garcia; Malgor, Emily A; Sobreira, Marcone Lima
Introduction: Treatment of cancer-associated venous thromboembolism (CAVTE) remains challenging. The aim of this study was to assess the outcomes of direct acting oral anticoagulants (DOAs) for the treatment of CAVTE. Materials and methods: A network meta-analysis of randomized clinical trials comparing DOAs (Apixaban, Rivaroxaban, and Edoxaban) versus Dalteparin for the treatment of CAVTE was performed. Outcomes of interest included, VTE recurrence, all-cause mortality, event-free survival, major bleeding, and clinically relevant non-major bleeding (CRNMB). Analysis was based on a random effects model and Bayesian Markov-chain Monte Carlo method was used for indirect comparisons. Results: Four RCTs involving 2894 patients were included. Overall certainty of evidence was moderate regarding all outcomes. DOAs exhibited lower risk of VTE (RR 0.62; 95% CI 0.44, 0.87; P = 0.007), similar risk of major bleeding (RR 1.33; 95% CI 0.84, 2.11; P = 0.23), and higher risk of CRNMB (RR 1.66, 95% CI 1.08, 2.56; P = 0.02), compared with Dalteparin. Risk of all-cause mortality and event-free survival were similar between groups with RR 0.99 (95% CI 0.84, 1.16) and RR 1.03 (95% CI 0.94, 1.13), respectively. Apixaban ranked first for recurrent VTE (42.4%) and major bleeding (62.3%) and Dalteparin ranked first for CRNMB (54.7%). Rivaroxaban ranked best considering all-cause mortality (58.7%); Apixaban ranked best for event-free survival (83.6%). Conclusions: DOAs presented a reduced risk of recurrent VTE with similar risk of major bleeding compared to Dalteparin. However, a higher risk of CRNMB is expected when this cohort of patients are treated with DOAs instead of Dalteparin.